Impact of a prior history of cancer on prognosis after myeloablative single-unit cord blood transplantation. (31st December 2020) - Okabe, Motohito; Konuma, Takaaki; Oiwa-Monna, Maki; Kato, Seiko; Isobe, Masamichi; Takahashi, Satoshi; Tojo, Arinobu
Abstract: A prior history of cancer was associated with higher non-relapse mortality or overall mortality in patients undergoing allogeneic haematopoietic cell transplantation. Because it is unclear whether the outcomes after cord blood transplantation are influenced by a prior history of cancer, we retrospectively assessed the prevalence and prognostic impact of a prior history of cancer in adult patients undergoing myeloablative single-unit cord blood transplantation in our institute between 2004 and 2020. The univariate analysis showed that a prior history of cancer did not affect the probability of overall survival; the cumulative incidence of relapse; or non-relapse mortality. In the multivariate analysis, prior history of cancer was not associated with overall mortality, relapse or non-relapse mortality. No patients with a prior history of cancer had experienced prior cancer relapse. A prior history of cancer was not associated with non-relapse mortality or overall mortality following single-unit cord blood transplantation. Abstract : Our retrospective study demonstrated that a prior history of cancer was not associated with mortality following single-unit cord blood transplantation.